Recognition of DNA modified by antitumor cisplatin by "latent" and "active" protein p53 - Fojta, Miroslav; Pivonkova, Hana; Brazdova, Marie; Kovarova, Lucie; Palecek, Emil; Pospisilova, Sarka; Vojtesek, Borivoj; Kasparkova, Jana; Brabec, Viktor (Biochemical pharmacology, 2003)
Tumor suppressor protein p53 possesses two DNA-binding sites. One that is located within its core domain is responsible for sequence-specific DNA binding of the protein, non-specific binding to internal segments of single- or double-stranded DNA, and to certain kinds of non-B DNA structures. The other that is contained in the C-terminus of the protein binds to damaged DNA. Binding of active, latent, and in vitro-activated p53 protein to DNA fragments modified by antitumor cisplatin was studied using electrophoretic mobility shift assay in agarose gels and immunoblotting analysis. We found that both latent and active p53 forms bound to random sequences of DNA globally modified by cisplatin with a higher affinity than to unmodified DNA. Interestingly, the latent form exhibited a more pronounced selectivity for platinated DNA than the active p53. Consistently with this observation, the preference of the latent form for platinated DNA decreased as a consequence of the activation of latent p53 by phosphorylation at the protein kinase C site within its C-terminus or by binding of the monoclonal antibody Bp53-10.1. Competition experiments involving a 20-bp consensus sequence of p53 suggested that the p53 core domain was a primary binding site of the active p53 when it bound to DNA fragments lacking consensus sequence, but modified by cisplatin. In addition, the latent protein was found to selectively interact with DNA modified by cisplatin probably via its C-terminus.
Keywords: transfekce; Recombinant Proteins; sekvence nukleotidů; Cell Line; vazebná místa; protinádorové látky; Transfection; fosforylace; Phosphorylation; nádorový supresorový protein p53; Oligodeoxyribonucleotides; rekombinantní proteiny; oligodeoxyribonukleotidy; Binding Sites; kinetika; Animals; Spodoptera; lidé; Humans; zvířata; DNA; buněčné linie; cisplatina; Base Sequence; Cisplatin; Kinetics; Tumor Suppressor Protein p53; Antineoplastic Agents